Pengembangan Media Pembelajaran Interaktif Articulate Storyline Berbasis Keterampilan Berpikir Kritis pada Pembelajaran IPA bagi Siswa Sekolah Dasar - Legina, Nadia; Sari, Prima Mutia (Jurnal Paedagogy, 2022)
This study aims to create a new product in the form of Articulate Storyline interactive learning media based on elementary school students' critical thinking skills in science learning. The study used Research & Development (R&D) and the ADDIE model, which had five stages: analysis, design, development, implementation, and evaluation. The data analysis technique in this study used qualitative & quantitative techniques. Qualitative data were obtained through interviews, comments, and suggestions—meanwhile, quantitative data were obtained through questionnaires to validators, educators, and students. The validation test results given by material experts had an average of 91% of the categories obtained as very feasible, and the validation test results given by media experts also had an average of 91%, including the very feasible category. The assessment results of educators' responses to the media obtained an average percentage of 93%, with an excellent category. The response of students' assessments to the media obtains an average percentage of 89% and found the category was outstanding. The data above proves that Articulate Storyline interactive learning media based on critical thinking skills in class V science learning for Elementary School students is suitable for the science learning process.